ETIKA DAN DAMPAK KOMODIFIKASI KOMUNIKASI DALAM INDUSTRI MEDIA MASSA - Setiadi, Muhammad Darmawan (Universitas 17 Agustus 1945 Surabaya, 2024)
ABSTRACT This research examines the ethics and impact of communication commodification in the mass media industry. The research method used is qualitative descriptive. The findings of the study indicate that practices in mass media communication are influenced by communication commodification, communication ethics, and relevant theories. Advertising and promotions are part of this commodification, where mass media sells ad space as commodities to companies or individuals for promotional purposes. This is related to the theory of communication commodification which reveals how communication is increasingly mediated by economic values and becomes a trading object in the media industry. Paid content is also popular in the digital era, where users pay to access specific content. Digital Ethics and Privacy emphasize the importance of maintaining privacy and ethics in digital practices, including payment and access to digital content. Sponsorship and endorsement practices are also part of this commodification, where media sells rights to support events or products to companies or individuals. Ethics in mass media communication practices can be seen from the perspective of Communication Ethics which includes principles such as truth, justice, responsibility, and integrity. The Hegemony and Media Control Theory describe how power and control in the mass media industry can influence the content produced, distributed, and consumed by the public. The commodification theory highlights the transformation of mass media into commercial products that require principles such as truth, impartiality, privacy, social justice, humanity, wisdom, integrity, and independence. The PEC theory emphasizes the relationship between economic and political structures and the production, distribution, and consumption of media, thus requiring principles such as independence from external pressure, truth in information, and social justice. Digital ethics and privacy are crucial in protecting user information and building public trust. Integrating these theories provides a more holistic understanding of the challenges and opportunities faced by the mass media industry in the modern era. Keywords: Communication Ethics; Mass Media Commodification; Media Economic Impact; Media Power